Special Event Logistics Geopolitical Event Bangkok - Gruenwald, Hermann (Information Management and Business Review, 2014)
Special event logistics covers a broad area from concerts, trade fairs, to public gatherings and beyond. This qualitative research is looking at special event logistics from a technical logistics management standpoint. The paper focuses on the logistics issues of the geopolitical events of the so called Shut down of Bangkok in 2014. The paper does not address the political issues surrounding the events and takes a neutral position only focusing on the technical logistics elements of the special event. Geopolitical special events are different as they involve thousands of volunteers at various levels of engagement over a more or less undetermined period of time with very fluid dynamics of the event. The emotions of the volunteers and participants are running high as it involves political and ideological viewpoints and therefore provides a high tension high pressure environment with a great level of uncertainty and risk. Supply chain risk management (SCRM) takes on a new meaning in the context of special events. Security is a major issue which goes beyond normal SCRM and business continuity planning. There needs to be access and crowd control as well as VIP and critical infrastructure protection. The logistics issues that need to be addressed include: site selection and preparation down to site dissolution, various sorts and types of assets and supplies from numerous and often daily varying sources need to be mobilized and demobilized. Infrastructure has to be provided and in some cases created including public utilities such as electricity, water, sewer, phone, fax, internet and mobile telephones, cable, wireless networks, satellite up and down links, to ATM machines which have to be brought to the site. Food and beverages (F&B) services range from drinking water to feeding thousands to special diets for vegetarians, Buddhist monks and Muslim participants. Storage on-site and off-site involves coldsupply chain (CSC) as well as perishable items and bulk items ranging from less than a truck load (LTL) to large bulk shipments. Audio visual (AV) services and multi-media needs to be covered both on a close circuit (CCTV) network for the site as well as national and international news and media coverage. There are also the demand planning and transportation issue, goods and people have to be transported to and from and in between often multiple venues which adds to the complexity.